Consistency of Findings Across International Surveys of Math & Science - O'Leary, Michael; Kellaghan, Thomas; Madaus, George; Beaton, Albert (Education Policy Analysis Archives, 2000)
The investigation reported in here was prompted by discrepancies between the performance of Irish students on two international tests of science achievement: the Second International Assessment of Educational Progress (IAEP2) administered in 1991 and the Third International Mathematics and Science Study (TIMSS) administered in 1995. While average science achievement for Irish 13-year-olds was reported to be at the low end of the distribution representing the 20 participating countries in IAEP2, it was around the middle of the distribution representing the 40 or so countries that participated in TIMSS at grades 7 and 8. An examination of the effect sizes associated with mean differences in performance on IAEP2 and TIMSS indicated that the largest differences are associated with the performance of students in France, Ireland and Switzerland. Five hypotheses are proposed to account for the differences.